ANALYSIS OF THE MARKETING EFFICIENCY OF THE RED CURLY CHILI (Capsicum annuum L.) IN KEPAHIANG DISTRICT - Pranata, Bagus Dwi; Badrudin, Redy; Romdhon, Mostopa (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
This Research is conducted in Kepahiang Regency. The location of the study is selected purposely (deliberately) by considering that the area is one of the production centers of curly red chili in Bengkulu Province. The purpose of this study is to analyze the marketing efficiency performed by the marketing agents of curly red chili in Kepahiang Regency. The samples in this study are 37 chili farmers, 11 collectors, 4 intercity traders, and 12 retailers who sell to the final consumer. This study uses primary data. Marketing efficiency is analyzed through marketing channel, analysis of marketing margin, and Farmer's share, as the efficiency measurement scale. The findings of this study indicate that the marketing of curly red chilies in Kepahiang Regency is categorized as Efficient.